Modifikasi Fantom ORNL_MIRD untuk Kebutuhan Simulasi Monte Carlo Pasien Radioterapi Kanker Payudara Menggunakan MCNPX - Layna Miska; Rini Safitri; Irwandi Irwandi; Elin Yusibani (Jurnal Rekayasa Elektrika, 2019)
In medical physics, the simulation of radiation dose distribution in the body of radiotherapy patients is generally carried out using the Monte Carlo method. But in conducting this simulation, medical physicists are often faced with the incompatibility problems of phantom geometry with simulation needs. Phantom ORNL-MIRD is the most commonly used phantom in simulation. In a radiotherapy simulation, cancer cells are usually only assumed to be in the phantom’s body without any concrete form. This can cause the administration of radiation doses that are not right on cancer cells. Phantom ORNL-MIRD is also only composed of three materials, namely bone, lung, and the rest are considered as soft tissue. This certainly provides inappropriate simulation results, especially in the case of breast cancer radiotherapy where the breast is composed of adipose tissue. This study aims to make ORNL_MIRD phantom modelling suitable for the needs of Monte Carlo simulations of breast cancer patients. The phantom modification will be carried out on the soft tissue structure of the breast and the structure of the skin tissue. Cancer cells with a diameter of 2 cm were also added to the left breast at a depth of 2.5 cm. The γ rays from radionuclide 60Co with the energy of 1.1732 MeV and 1.3325 MeV and the probabilities of 0.989 and 0.998, respectively, were exposed to the phantom. The simulation results show that there are significant differences before and after modification. Absorption dose values in the breast with a soft tissue without tumour cells were 0.31 mGy with a relative error of 0.0023, while the absorbency dose rate in the breast with soft tissue and tumour cells was 0.2 mGy with a relative error of 0.0023.